The potential use of Octolasmis spp. parasites in mud crabs Scylla spp. as a bioindicator for mercury pollution (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nur I, Aris EA, Yusnaini Y, Beavis S. 2021. The potential use of Octolasmis spp. parasites in mud crabs Scylla spp. as a bioindicator for mercury pollution. Biodiversitas 22: 3764-3772. Artisanal small-scale gold mining and the use of mercury is widespread across Indonesia, often characterized by relatively short-lived gold rushes. In the late and post-mining phases, mercury stored in mine tailings and river beds was transported down catchment, posing risks to ecosystems and human health over much longer time scales. These risks can be under-rated when mercury concentrations in water, sediments, and aquatic species are low enough to meet relevant guideline thresholds. In this study in Southeast Sulawesi, Indonesia, we have investigated the Costraca barnacle, Octolasmis, as a bioindicator of mercury contamination. The presence of Octolasmis parasites in mud crabs, Scylla spp., and the accumulation of mercury (Hg) in the hosts, parasites, and the ambient environment, were analyzed across both dry and wet seasons. Severe infestation of Octolasmis was assessed using prevalence, abundance, and intensity. Hg concentrations were significantly higher in the Octolasmis parasites than in the host tissues, water and sediments. The mean bioconcentration factor (BCF) of Hg equaled 7938.21 from water to parasites, and 28.91 from the host’s gill tissue to the parasites. The results suggest that Octolasmis spp. can be used effectively as a bioindicator in coastal catchments impacted by mercury contamination, even when concentrations of mercury are low in water and river sediments. The study provides the first report of Octolasmis spp. parasitized to mud crabs as a reliable bioindicator of Hg contamination and pollution.
Keywords: Bioindicator; mangrove; mud crab; parasite; artisanal small scale gold mining; pollution